[When I care about others - Spelman, Cornelia Maude; Parkinson, Kathy ([S.l.] : [Bradon-Chinese Media Agency], 2005)
A little bear explains that he cares about the feelings of others and that others care about him. Presented in English and Chinese.
K-3
Text in English and Chinese.
Translated from the English.
Title taken from t.p. verso; title on title page is in Chinese characters.
Keywords: Caring -- Juvenile fiction; Sympathy -- Juvenile fiction; Bears -- Juvenile fiction; Caring -- Fiction; Sympathy -- Fiction; Chinese language materials -- Bilingual; Bears -- Fiction; Caring -- Fiction; Sympathy -- Fiction; Bilingual books -- English-Chinese.; Bears -- Fiction